EKSTRAKSI KALIUM DARI KULIT BUAH KAPUK (Ceiba petandra) - Chandra Sitorus, Lilis Sukeksi, Andy Junianto Sidabutar (Jurnal Teknik Kimia USU, 2018)
The purpose of this study was to determine the best  of combustion time and temperature of ash production from kapok fruit peel ( Ceiba Petandra ) to get the most potassium. The experiment was begun to dry kapok  fruit peel for 24 hours at oven with temperature 110 oC and combustion to obtaine the ash from kapok fruit peel. The combustion was done by muffle furnace which time variables were from  3 hours, 4 hours, 5 hours, and 6 hours and burning temperature variables were from, 500 oC, 550 oC,600 oC, 650oC. The potassium that contained in ash have been extracted by distilled water with volume 30 ml  for 24 hours. Observed responses were normality, pH, ash content,  and potassium oxide content (% K2O). The best result of ash was in 3 hours with temperature 500 oC. The ash was analyzed by using AAS Atomic Absorption Spectroscopy, and 35.91 % of potassium oxide (K2O) content was obtained as maximum result.